ROLE OF POTAKI MOOLA KALKA LEPANA IN PRASAVA (1ST STAGE OF LABOUR): A COMPARATIVE STUDY (International Journal of Ayurveda and Pharma Research, 2020)
Pregnancy, parturition and puerperium are the three main stages occurring during active reproductive period of a woman’s life. Among them, parturition is the stage that needs highest attention. Labour is a nature’s process. Very often it requires minimal assistance. However, due to altered anatomy and physiology a perfectly normal labour may suddenly become abnormal and even fatal. Objectives: To evaluate the effect of Potaki Moola Kalka Yoni Lepana in Prasava (First stage of labour) Design: This was a randomized controlled study with thirty patients divided into two groups, 15 in each. In Group A, Prostaglandin E2 (Dinoprostone gel) was administered vaginally for maximum of 3 doses with a gap of 6hrs and in Group B, Pothaki moola kalka application was done was vaginally for maximum of 3 Lepa application with a gap of 6hrs. Results: Statistically significant results were seen in cervical dilatation, cervical effacement, cervical position, cervical consistency and head station components of Bishop’s score in the first stage of labor with p < 0.05. Conclusions: Group B showed statistically significant results in cervical dilatation, cervical effacement, cervical position, cervical consistency, head station etc, components of Bishop’s score in the first stage of labor compared to Group A.